2011
DOI: 10.1902/jop.2010.100454
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Enamel Matrix Derivative Protein in Minimally Invasive Surgery in Treating Intrabony Defects in Single‐Rooted Teeth: A Randomized Clinical Trial

Abstract: The use of EMD did not provide superior benefits on the outcome of the minimally invasive surgical approach for the treatment of intrabony defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
3
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(96 citation statements)
references
References 39 publications
6
83
3
4
Order By: Relevance
“…() concerning the papilla preservation flap methods (2.48 mm, CI: 1.44–3.52). The present findings are also more favourable with respect to those reported in controlled clinical trials evaluating the outcomes of regenerative surgery in intrabony defects using enamel matrix derivative and minimally invasive surgery (Cortellini & Tonetti, ; Jepsen et al., ; Ribeiro, Casarin, Jùnior, Sallum, & Casati, ). At 12 months they reported CAL changes ranging from 1.8 to 4.9 mm and PD reduction from 2.6 to 5.2 mm.…”
Section: Discussionsupporting
confidence: 74%
“…() concerning the papilla preservation flap methods (2.48 mm, CI: 1.44–3.52). The present findings are also more favourable with respect to those reported in controlled clinical trials evaluating the outcomes of regenerative surgery in intrabony defects using enamel matrix derivative and minimally invasive surgery (Cortellini & Tonetti, ; Jepsen et al., ; Ribeiro, Casarin, Jùnior, Sallum, & Casati, ). At 12 months they reported CAL changes ranging from 1.8 to 4.9 mm and PD reduction from 2.6 to 5.2 mm.…”
Section: Discussionsupporting
confidence: 74%
“…Amelogenin, a 20 kDa hydrophobic protein, is the chief ingredient in the EMD. Studies have shown that amelogenin promotes healing and regeneration of the supporting structures of teeth including cementum (3,4). Similar results were reported by Berlucchi et al (5).…”
Section: Introductionsupporting
confidence: 84%
“…In other studies (Cortellini & Tonetti , Ribeiro et al. ,b) comparing M‐MIST with M‐MIST+EMD and MIST with MIST+EMD, no inter‐group significance was reported.…”
Section: Discussionmentioning
confidence: 86%